High-flame-retardant composite material for FPC (Flexible Printed Circuit) reinforcing plate and preparation method of high-flame-retardant composite material
By using high flame retardant composite materials in FPC reinforcement plates, combined with modified glass fibers and synergistic flame retardant, the problem of insufficient strength and flame retardant performance of existing FPC reinforcement plates is solved, and excellent mechanical properties and flame retardant performance are achieved.
Patent Information
- Application Number
- CN202510078666.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-17
- Publication Date
- 2025-04-18
AI Technical Summary
The strength and flame retardant performance of existing FPC reinforcement plates are insufficient, making it difficult to meet market demand.
A highly flame retardant composite material is adopted, including nylon 66, modified 2-carboxyethylphenylphosphate, modified hexaphenoxycyclotriphosphazene, modified glass fiber, coupling agent, antioxidant and lubricant. Through the special treatment of modified glass fiber and the synergistic effect of flame retardant, the mechanical properties and flame retardant properties of the composite material are significantly improved.
The excellent mechanical properties and significant flame retardant properties of the composite material are achieved, making it suitable for the application needs of FPC reinforcement plates.
Smart Images

Figure BDA0005247848040000081
Abstract
Description
Technical Field
[0001] The present application relates to the field of flexible circuit boards, and in particular to a highly flame-retardant composite material for an FPC reinforcement plate and a preparation method thereof. Background Art
[0002] Flexible printed circuit board (hereinafter referred to as FPC), as a special electronic interconnection technology, has very significant advantages. It is light, thin, short, small, high density, high stability, and flexible in structure. It is widely used in civil appliances, computers, computer peripheral auxiliary systems, digital products, medical equipment, automobile fields, as well as military and complex aerospace fields.
[0003] Due to the characteristics of FPC boards being light, thin, short and small, there is a process of attaching reinforcement boards during the production process. Various reinforcement boards are attached to the FPC boards to enhance the support capacity of the FPC boards and improve the flame retardant effect. The strength and flame retardant performance of the current FPC reinforcement boards need to be improved to better meet market demand. Summary of the invention
[0004] In view of the deficiencies in the prior art, the present application provides a highly flame-retardant composite material for an FPC reinforcement plate and a preparation method thereof. The highly flame-retardant composite material for an FPC reinforcement plate prepared in the present application has excellent mechanical properties and flame-retardant properties.
[0005] In the first aspect, the present application provides a highly flame-retardant composite material for an FPC reinforcement plate, adopting the following technical scheme: a highly flame-retardant composite material for an FPC reinforcement plate, comprising the following preparation raw materials, by mass: 95-100 parts of nylon 66, 12-14 parts of a flame retardant, 3-6 parts of a toughening agent, 22-25 parts of modified glass fiber, 1-1.5 parts of a coupling agent, 0.3-0.5 parts of an antioxidant, and 0.4-0.6 parts of a lubricant, wherein the flame retardant is composed of modified 2-carboxyethylphenyl hypophosphorous acid and modified hexaphenoxycyclotriphosphazene.
[0006] By adopting the above technical scheme, nylon 66 is used as the matrix resin to provide good mechanical strength and toughness, and is the main skeleton of the composite material. Flame retardant: Modified 2-carboxyethylphenylphosphorous acid is modified by decanediamine to generate amide bonds and phosphonates, which improves flame retardancy and stability, while reducing the negative impact on mechanical properties. Modified hexaphenoxy cyclotriphosphazene has excellent flame retardancy, thermal stability and low smoke generation. After modification, it can be grafted onto the surface of nano-silica to further enhance the flame retardant effect. The two flame retardants work synergistically to significantly improve the flame retardant and mechanical properties of the composite material. The toughening agent improves the toughness of the material and prevents brittle cracking caused by excessive rigidity. Modified glass fiber: The glass fiber is treated with hydrogen peroxide, composited with polydimethyldiallylammonium chloride, composited with nano-silica and modified with vinyltriethoxysilane to enhance the dispersibility and compatibility of the glass fiber, thereby significantly improving the mechanical properties and flame retardant properties of the composite material. Coupling agent: Promotes the interface bonding between different components, improves the uniformity and stability of the overall material and improves the comprehensive performance. Antioxidants prevent materials from oxidative degradation at high temperatures and extend their service life. Lubricants improve material processing properties, reduce friction resistance, and facilitate molding. Flame retardants and glass fibers: Modified flame retardants and modified glass fibers work synergistically to significantly improve the flame retardant and mechanical properties of composite materials. Flame retardants enhance the compatibility and stability with the matrix resin through chemical modification, while modified glass fibers further enhance the overall performance of composite materials by improving dispersibility and compatibility. Tougheners, coupling agents, antioxidants, and lubricants optimize the comprehensive properties of composite materials, such as toughness, processing properties, and durability, through their respective effects. In summary, each component plays an important role in the composite material, and through the synergistic effect, the mechanical properties and flame retardant properties of the material are significantly improved, making it suitable for the application requirements of FPC reinforcement plates.
[0007] Preferably, the mass ratio of the modified 2-carboxyethylphenyl hypophosphorous acid to the modified hexaphenoxycyclotriphosphazene is 2:3.
[0008] By adopting the above technical scheme, modified 2-carboxyethylphenyl hypophosphorous acid: This flame retardant is modified by decanediamine to generate amide bonds and phosphonates, which effectively solves the problem of decreased mechanical properties caused by using 2-carboxyethylphenyl hypophosphorous acid alone. It not only improves the flame retardancy of the composite material, but also enhances the stability of the material. Modified hexaphenoxy cyclotriphosphazene: This is a phosphorus-nitrogen type flame retardant with a unique PN hybrid structure, which gives it excellent flame retardant properties, thermal stability, water resistance and antioxidant properties. In addition, the amount of smoke generated during combustion is low. The modified hexaphenoxy cyclotriphosphazene can also be grafted to the surface of nano-silica through a silane coupling agent to further enhance the flame retardant effect and mechanical properties of the composite material. When modified 2-carboxyethylphenyl hypophosphorous acid and modified hexaphenoxy cyclotriphosphazene are mixed in a mass ratio of 2:3, the two show a significant synergistic effect. The modified 2-carboxyethylphenylphosphite mainly contributes to improving the stability and flame retardancy of the material, while the modified hexaphenoxycyclotriphosphazene further enhances the flame retardancy and mechanical properties of the composite material through its unique structure and modification technology. This synergistic effect enables the composite material to achieve higher flame retardancy standards while maintaining good mechanical properties. In summary, the synergistic effect of these two flame retardants is to optimize their mass fraction ratio (2:3) and give full play to their respective advantages, thereby significantly improving the overall performance of the composite material, especially the flame retardancy and mechanical properties.
[0009] Preferably, the preparation method of the modified 2-carboxyethylphenyl hypophosphorous acid is as follows: 40 parts of decanediamine are placed in 80 parts of water according to the mass fraction, and the mixture is cooled and stirred at a temperature of 4°C, a stirring rate of 200-250 r / min, and a stirring time of 70-80 min to obtain a mixed solution; then 30 parts of 2-carboxyethylphenyl hypophosphorous acid are added to the mixed solution, and the mixture is heated and stirred at a temperature of 85°C, a stirring rate of 200-250 r / min, and a stirring time of 10-12 h. After cooling to room temperature, the mixture is filtered, washed, and dried at 90°C for 10 h to obtain the modified 2-carboxyethylphenyl hypophosphorous acid.
[0010] By adopting the above technical scheme, the prepared modified 2-carboxyethylphenyl hypophosphorous acid is prepared by modifying 2-carboxyethylphenyl hypophosphorous acid with decanediamine, and the amino group (-NH2) of decanediamine reacts with the carboxylic acid group (-COOH) of 2-carboxyethylphenyl hypophosphorous acid to generate an amide bond (-CONH-), and can also react with the hypophosphorous acid group (-PO(OH)H) of 2-carboxyethylphenyl hypophosphorous acid to form a phosphonate, thereby solving the problem of poor mechanical properties caused by adding 2-carboxyethylphenyl hypophosphorous acid into nylon 66, and effectively improving the flame retardancy and stability of the composite material.
[0011] Preferably, the preparation method of the modified hexaphenoxy cyclotriphosphazene comprises the following steps: S41, according to the mass parts, 693 parts of hexaphenoxy cyclotriphosphazene and 124 parts of γ-(methacryloyloxy)propyltrimethoxysilane are added to 1200 parts of acetone, and heated to 75-80°C under nitrogen protection, and kept warm for 1-1.3 hours, then, 0.8 parts of azobisisoheptanenitrile are dissolved in 20 parts of acetone to obtain an azobisisoheptanenitrile solution, and the azobisisoheptanenitrile solution is slowly added dropwise within 1 hour, and then after reacting for 10-12 hours, the acetone is removed by rotary evaporation to obtain γ-(methacryloyloxy)propyltrimethoxysilane-modified hexaphenoxy cyclotriphosphazene; S42. Dry nano-silica with a particle size of 20-30 nm at 100-120°C for 6-8h according to the mass fraction, then add 50 parts of the dried nano-silica and 200 parts of γ-(methacryloyloxy)propyltrimethoxysilane-modified hexaphenoxycyclotriphosphazene to 1500 parts of anhydrous ethanol, stir evenly, and reflux at 78-82°C for 16-20h under nitrogen protection. After the reaction is completed, filter, wash with ethanol, and dry to obtain modified hexaphenoxycyclotriphosphazene.
[0012] By adopting the above technical scheme, hexaphenoxy cyclotriphosphazene belongs to phosphorus-nitrogen flame retardant, which has a unique PN hybrid structure, giving it excellent flame retardant properties and high thermal stability, and has the characteristics of water resistance, oxidation resistance and low smoke generation during combustion. In addition, hexaphenoxy cyclotriphosphazene can be chemically grafted to the surface of nano-silica particles after being modified by silane coupling agent to prepare a new type of phosphorus-nitrogen nano flame retardant, and applied to composite materials. Since silica nanoparticles can significantly improve the combustion properties of composite materials such as heat release rate, organic phosphorus-nitrogen and nanoparticles have obvious synergistic flame retardant effects, significantly improving the mechanical properties and flame retardant properties of composite materials.
[0013] Preferably, the method for preparing the modified glass fiber comprises the following steps: S51. According to the mass fraction, 100 parts of chopped glass fibers with a length of 3-4 mm and a diameter of 9-12 μm are placed in 350 parts of a 25% hydrogen peroxide solution, and then heated at 105-110° C. for reaction for 3-4 hours; after the reaction is completed, the pre-modified glass fibers are obtained by filtering and drying; S52, according to the mass fraction, put 100 parts of the pre-modified glass fiber into 1000 parts of a polydimethyldiallylammonium chloride aqueous solution with a mass concentration of 3.5-4.0%, stir for 1-2 hours, filter, wash and dry to obtain the pre-modified glass fiber; S53. Disperse 50 parts of silica with an average particle size of 20-30 nanometers and 100 parts of pre-modified glass fibers in a solution consisting of 200 parts of ethanol and 500 parts of water, and stir for 2-3 hours. Then, add 3.5 parts of vinyltriethoxysilane, adjust the pH of the solution to 5-6, stir for 4-5 hours, and obtain modified glass fibers by centrifugation, washing, and drying.
[0014] By adopting the above technical scheme, glass fiber is often used to improve the tensile strength, impact strength and other properties of nylon, but glass fiber is difficult to disperse and has poor compatibility. Therefore, the glass fiber is specially modified in the present application, specifically: the glass fiber is first treated with hydrogen peroxide, then compounded with polydimethyldiallyl ammonium chloride, then compounded with nano-silica, and finally modified with vinyltriethoxysilane; hydrogen peroxide treatment of the glass fiber can cause oxidation on its surface, enhance its surface activity, and is beneficial to the subsequent compounding of polydimethyldiallyl ammonium chloride. The positive charge characteristics of polydimethyldiallyl ammonium chloride and the nano-silica with negative surface charge can be effectively compounded and combined; and the hydroxyl groups on the surface of the glass fiber after the nano-silica and hydrogen peroxide treatment can produce hydrogen bonds with the polydimethyldiallyl ammonium chloride in pairs, thereby strengthening the stability of the compounding system. Finally, the modified glass fiber is modified with vinyltriethoxysilane, which can significantly improve the dispersibility and compatibility of the modified wear-resistant glass fiber, thereby significantly improving the mechanical properties and flame retardant properties of the composite material.
[0015] Preferably, the coupling agent is composed of γ-aminopropyltrimethoxysilane, anilinemethyltriethoxysilane and N-aminoethyl-γ-aminopropyltriethoxysilane in a mass ratio of 3:3:2.
[0016] By adopting the above technical scheme, these three silane coupling agents can form a stable chemical bond between the nylon 66 matrix and the inorganic filler (such as modified glass fiber), thereby improving the compatibility and interfacial bonding between the two. This effect helps to reduce the defects and pores inside the composite material and improve the overall mechanical properties. Through the synergistic effect with flame retardants (such as modified 2-carboxyethylphenyl hypophosphite and modified hexaphenoxy cyclotriphosphazene), these coupling agents can promote the uniform dispersion of flame retardants in composite materials and improve flame retardant efficiency. These coupling agents can also improve the processing properties of composite materials, such as improving melt fluidity, reducing molding shrinkage, etc., which is beneficial to the production and manufacturing of FPC reinforcement plates. γ-aminopropyl trimethoxysilane, aniline methyl triethoxysilane and N-aminoethyl-γ-aminopropyl triethoxysilane each contain different active functional groups (such as amino, aniline, etc.), which can form multiple cross-linked networks with multiple components such as nylon 66 matrix, flame retardant, modified glass fiber, etc., thereby achieving a synergistic enhancement effect. Through the above-mentioned synergistic effect, these coupling agents can not only play their respective roles individually, but also cooperate with each other to jointly optimize the mechanical properties, flame retardant properties and processing properties of the composite materials, achieving the best balance of comprehensive performance.
[0017] Preferably, the lubricant is PE wax.
[0018] Preferably, the toughening agent is maleic anhydride grafted ultra-low density polyethylene, and the mass percentage of maleic anhydride groups in the maleic anhydride grafted ultra-low density polyethylene is 1-2%.
[0019] Preferably, the antioxidant is bis(2,4-dicumylphenyl)pentaerythritol diphosphite.
[0020] In a second aspect, the present application provides a method for preparing a highly flame-retardant composite material for an FPC reinforcement plate, using the following technical solution: As a general technical concept, the present application also provides a method for preparing the above-mentioned highly flame-retardant composite material for FPC reinforcement plate, comprising the following steps: S101, adding each raw material into a high-speed mixer according to the mass fraction and mixing them evenly to obtain a premix; S102, melting the premix at an extrusion temperature of 260-275° C. in a twin-screw extruder, extruding and granulating the premix at a rotation speed of 400-450 rpm in the twin-screw extruder, and obtaining a highly flame-retardant composite material for an FPC reinforcement plate.
[0021] In summary, the present application includes at least one of the following beneficial technical effects: 1. Excellent mechanical properties: Through the synergistic effect of specially modified glass fiber and other raw materials, the prepared composite material has excellent mechanical properties, including good tensile strength and impact strength.
[0022] 2. Significant flame retardant properties: The synergistic effect of modified 2-carboxyethylphenyl hypophosphorous acid and modified hexaphenoxy cyclotriphosphazene significantly improves the flame retardant properties of the composite material. Both modified substances have unique chemical structures and flame retardant properties, which can effectively slow down the burning speed of the material and reduce the amount of smoke and toxic gases generated during combustion.
[0023] 3. High stability: During the preparation process, composite materials are optimized with a variety of modification technologies and raw materials, making the materials have high stability and durability, including stability to environmental factors such as temperature and humidity, and durability for long-term use. DETAILED DESCRIPTION
[0024] The embodiments of the present application will be described in detail below in conjunction with the examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. In the examples, if specific conditions are not specified, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0025] In the following examples and preparation examples, 1 part means 100 g.
[0026] Preparation Example 1 Preparation of modified 2-carboxyethylphenyl hypophosphorous acid The preparation method of modified 2-carboxyethylphenyl hypophosphorous acid is as follows: according to the mass fraction, 40 parts of decanediamine are placed in 80 parts of water, and the mixture is cooled and stirred at a temperature of 4°C, a stirring rate of 220 r / min, and a stirring time of 75 min to obtain a mixed solution; then 30 parts of 2-carboxyethylphenyl hypophosphorous acid are added to the mixed solution, and the mixture is heated and stirred at a temperature of 85°C, a stirring rate of 220 r / min, and a stirring time of 11 h. After cooling to room temperature, the mixture is filtered, washed, and dried at 90°C for 10 h to obtain modified 2-carboxyethylphenyl hypophosphorous acid.
[0027] Preparation Example 2 Preparation of modified hexaphenoxy cyclotriphosphazene The preparation method of modified hexaphenoxy cyclotriphosphazene comprises the following steps: S41. According to the mass fractions, 693 parts of hexaphenoxy cyclotriphosphazene and 124 parts of γ-(methacryloyloxy)propyltrimethoxysilane are added to 1200 parts of acetone, and the temperature is raised to 80° C. under nitrogen protection, and the temperature is kept for 1 hour. Then, 0.8 parts of azobisisoheptanenitrile are dissolved in 20 parts of acetone to obtain an azobisisoheptanenitrile solution, and the azobisisoheptanenitrile solution is slowly added dropwise within 1 hour. After reacting for 12 hours, the acetone is removed by rotary evaporation to obtain γ-(methacryloyloxy)propyltrimethoxysilane-modified hexaphenoxy cyclotriphosphazene; S42. Dry nano-silica with an average particle size of 25 nanometers at 110°C for 7 hours according to the mass fraction, then add 50 parts of the dried nano-silica and 200 parts of γ-(methacryloyloxy)propyltrimethoxysilane-modified hexaphenoxycyclotriphosphazene to 1500 parts of anhydrous ethanol, stir evenly, and reflux at 80°C for 18 hours under nitrogen protection. After the reaction is completed, filter, wash with ethanol, and dry to obtain modified hexaphenoxycyclotriphosphazene.
[0028] Preparation Example 3 Preparation of modified glass fiber The preparation method of modified glass fiber comprises the following steps: S51. According to the mass fraction, 100 parts of chopped glass fibers with a length of 3-4 mm and a diameter of 9-12 μm are placed in 350 parts of a 25% hydrogen peroxide solution, and then heated at 110° C. for reaction for 3 hours; after the reaction is completed, the pre-modified glass fibers are obtained by filtering and drying; S52, according to the mass fraction, put 100 parts of the pre-modified glass fiber into 1000 parts of a 3.8% polydimethyldiallylammonium chloride aqueous solution, stir for 1.2 hours, filter, wash, and dry to obtain the pre-modified glass fiber; S53. According to the mass proportions, 50 parts of silica with an average particle size of 25 nanometers and 100 parts of pre-modified glass fibers are dispersed in a solution consisting of 200 parts of ethanol and 500 parts of water and stirred for 3 hours. Then, 3.5 parts of vinyltriethoxysilane are added thereto, and the pH of the solution is adjusted to 5. The solution is stirred for 5 hours. After centrifugation, washing and drying, modified glass fibers are obtained.
[0029] Example 1 A highly flame-retardant composite material for an FPC reinforcing plate comprises the following raw materials by weight: 95 parts of nylon 66, 12 parts of a flame retardant, 3 parts of a toughening agent, 22 parts of modified glass fiber, 1 part of a coupling agent, 0.3 parts of bis(2,4-dicumylphenyl)pentaerythritol diphosphite, and 0.4 parts of PE wax. The flame retardant is composed of modified 2-carboxyethylphenyl hypophosphorous acid and modified hexaphenoxy cyclotriphosphazene in a weight ratio of 2:3. The coupling agent is composed of γ-aminopropyltrimethoxysilane, anilinemethyltriethoxysilane, and N-aminoethyl-γ-aminopropyltriethoxysilane in a weight ratio of 3:3:2. The toughening agent is maleic anhydride grafted ultra-low density polyethylene, and the mass percentage of maleic anhydride groups in the maleic anhydride grafted ultra-low density polyethylene is 1%. The preparation method of the highly flame-retardant composite material for an FPC reinforcing plate comprises the following steps: S101, adding each raw material into a high-speed mixer according to the mass fraction and mixing them evenly to obtain a premix; S102, melting the premix at an extrusion temperature of 260° C. in a twin-screw extruder, extruding and granulating the premix at a rotation speed of 450 rpm to obtain a highly flame-retardant composite material for an FPC reinforcement plate.
[0030] Example 2 A highly flame-retardant composite material for an FPC reinforcing plate, comprising the following raw materials by weight: 100 parts of nylon 66, 14 parts of a flame retardant, 6 parts of a toughening agent, 25 parts of modified glass fiber, 1.5 parts of a coupling agent, 0.5 parts of bis(2,4-dicumylphenyl)pentaerythritol diphosphite, and 0.6 parts of PE wax, wherein the flame retardant is composed of modified 2-carboxyethylphenyl hypophosphorous acid and modified hexaphenoxycyclotriphosphazene in a weight ratio of 2:3, the coupling agent is composed of γ-aminopropyltrimethoxysilane, anilinemethyltriethoxysilane, and N-aminoethyl-γ-aminopropyltriethoxysilane in a weight ratio of 3:3:2, and the toughening agent is maleic anhydride grafted ultra-low density polyethylene, and the mass percentage of maleic anhydride groups in the maleic anhydride grafted ultra-low density polyethylene is 1%; The method for preparing the highly flame-retardant composite material for the FPC reinforcement plate comprises the following steps: S101, adding each raw material into a high-speed mixer according to the mass fraction and mixing them evenly to obtain a premix; S102, melting the premix at an extrusion temperature of 275° C. in a twin-screw extruder, extruding and granulating the premix at a rotation speed of 400 rpm to obtain a highly flame-retardant composite material for an FPC reinforcement plate.
[0031] Example 3 A highly flame-retardant composite material for an FPC reinforcing plate comprises the following raw materials by weight: 98 parts of nylon 66, 13 parts of a flame retardant, 4 parts of a toughening agent, 24 parts of modified glass fiber, 1.4 parts of a coupling agent, 0.4 parts of bis(2,4-dicumylphenyl)pentaerythritol diphosphite, and 0.5 parts of PE wax. The flame retardant is composed of modified 2-carboxyethylphenyl hypophosphorous acid and modified hexaphenoxy cyclotriphosphazene in a weight ratio of 2:3. The coupling agent is composed of γ-aminopropyltrimethoxysilane, anilinemethyltriethoxysilane, and N-aminoethyl-γ-aminopropyltriethoxysilane in a weight ratio of 3:3:2. The toughening agent is maleic anhydride grafted ultra-low density polyethylene, and the mass percentage of maleic anhydride groups in the maleic anhydride grafted ultra-low density polyethylene is 1%. The preparation method of the highly flame-retardant composite material for an FPC reinforcing plate comprises the following steps: S101, adding each raw material into a high-speed mixer according to the mass fraction and mixing them evenly to obtain a premix; S102, melting the premix at an extrusion temperature of 268° C. in a twin-screw extruder, extruding and granulating the premix at a rotation speed of 430 rpm to obtain a highly flame-retardant composite material for an FPC reinforcement plate.
[0032] Comparative Example 1 The same as Example 3, except that an equal amount of a mixture (made by mixing short glass fibers having a length of 3-4 mm and a diameter of 9-12 μm and silicon dioxide having an average particle size of 25 nm in a mass ratio of 2:1) is used instead of the modified glass fibers.
[0033] Comparative Example 2 The same as Example 3, except that: the flame retardant is modified 2-carboxyethylphenyl hypophosphorous acid.
[0034] Comparative Example 3 The same as Example 3, except that: the flame retardant is modified hexaphenoxy cyclotriphosphazene.
[0035] Comparative Example 4 The same as Example 3, except that: the coupling agent is γ-aminopropyltrimethoxysilane.
[0036] Comparative Example 5 The same as Example 3, except that: the coupling agent is anilinemethyltriethoxysilane.
[0037] Comparative Example 6 The same as Example 3, except that: the coupling agent is N-aminoethyl-γ-aminopropyltriethoxysilane.
[0038] Performance testing The highly flame-retardant composite materials for FPC reinforcement plates prepared in Examples 1 to 3 and Comparative Examples 1 to 6 were sampled and injection-molded into test bars, and the following tests were performed. The results are shown in Table 1.
[0039] Tensile strength: tested according to GB / T 1040.2-2022 standard, the tensile rate is 50mm / min; Notched impact strength: tested according to GB / T1843-2008 standard; Flame retardant: UL-94 (3.2mm, 1.2mm, 0.6mm) detection method refers to the standard GB / T 2408-2008 / IEC for testing; the limiting oxygen index test refers to the standard ASTM-D2863 for testing.
[0040] Table 1 Performance test Analyzing the data in Table 1, we can see that: 1) The highly flame-retardant composite materials for FPC reinforcement plates prepared in Examples 1 to 3 have excellent mechanical properties and flame-retardant properties, making them suitable for the application requirements of FPC reinforcement plates.
[0041] 2) The performance comparison analysis of the highly flame-retardant composite material for FPC reinforcement plate prepared in Example 3 and Comparative Example 1 shows that the modified glass fiber prepared in the present application is first treated with hydrogen peroxide, then compounded with polydimethyldiallyl ammonium chloride, and then compounded with nano-silica, and finally modified with vinyltriethoxysilane; hydrogen peroxide treatment of the glass fiber can cause oxidation on its surface, enhance its surface activity, and is beneficial to the subsequent compounding of polydimethyldiallyl ammonium chloride. The positive charge characteristics of polydimethyldiallyl ammonium chloride and the nano-silica with negative surface charge can be effectively compounded and combined; and the hydroxyl groups on the surface of the glass fiber after nano-silica and hydrogen peroxide treatment can produce hydrogen bonds with polydimethyldiallyl ammonium chloride in pairs, thereby enhancing the stability of the compounding system. Finally, modification with vinyltriethoxysilane can significantly improve the dispersibility and compatibility of the modified wear-resistant glass fiber, thereby significantly improving the mechanical properties and flame retardant properties of the composite material.
[0042] 3) The performance comparison analysis of the highly flame-retardant composite material for FPC reinforcement plate prepared in Example 3 and Comparative Examples 2-3 shows that the flame retardant modified 2-carboxyethylphenyl hypophosphorous acid and modified hexaphenoxy cyclotriphosphazene are composed of a mass fraction ratio of 2:3, and the synergistic effect between them is utilized: the modified 2-carboxyethylphenyl hypophosphorous acid mainly contributes to improving the stability and flame retardancy of the material, while the modified hexaphenoxy cyclotriphosphazene further enhances the flame retardancy and mechanical properties of the composite material through its unique structure and modification technology. This synergistic effect gives full play to their respective advantages, thereby significantly improving the overall performance of the composite material, especially the flame retardancy and mechanical properties.
[0043] 4) The performance comparison analysis of the high flame retardant composite material for FPC reinforcement plate prepared by Example 3 and Comparative Examples 4-6 shows that the coupling agent is composed of γ-aminopropyl trimethoxysilane, aniline methyl triethoxysilane and N-aminoethyl-γ-aminopropyl triethoxysilane in a mass ratio of 3:3:2. These three silane coupling agents can form a stable chemical bond between the nylon 66 matrix and the inorganic filler (such as modified glass fiber), thereby improving the compatibility and interfacial bonding of the two. This effect helps to reduce the defects and pores inside the composite material and improve the overall mechanical properties. Through the synergistic effect with flame retardants (such as modified 2-carboxyethyl phenyl hypophosphite and modified hexaphenoxy cyclotriphosphazene), these coupling agents can promote the uniform dispersion of flame retardants in the composite material and improve the flame retardant efficiency. In addition, they can also form a dense protective layer during the combustion process to prevent the spread of flames and further enhance the flame retardant properties of the composite material. γ-Aminopropyltrimethoxysilane, anilinemethyltriethoxysilane and N-aminoethyl-γ-aminopropyltriethoxysilane each contain different active functional groups (such as amino, aniline, etc.). These functional groups can form multiple cross-linked networks with nylon 66 matrix, flame retardant, modified glass fiber and other components to jointly optimize the mechanical properties, flame retardant properties and processing properties of the composite materials, achieving the best balance of comprehensive performance.
[0044] The above embodiments are only used to explain the technical solutions of the present application rather than to limit them. Although the above embodiments provide a specific description of the present application, relevant technical personnel should understand that the specific implementation methods of the present application can still be modified or replaced by equivalents, and any modifications and equivalent replacements that do not depart from the spirit and scope of the present application should be included in the protection scope of the present application.
Claims
1. A highly flame-retardant composite material for an FPC reinforcement plate, characterized in that: The preparation material comprises the following raw materials by weight: 95-100 parts of nylon 66, 12-14 parts of flame retardant, 3-6 parts of toughening agent, 22-25 parts of modified glass fiber, 1-1.5 parts of coupling agent, 0.3-0.5 parts of antioxidant and 0.4-0.6 parts of lubricant, wherein the flame retardant is composed of modified 2-carboxyethylphenyl hypophosphorous acid and modified hexaphenoxy cyclotriphosphazene.
2. The highly flame-retardant composite material for FPC reinforcement plate according to claim 1, characterized in that: The mass ratio of the modified 2-carboxyethylphenyl hypophosphorous acid to the modified hexaphenoxy cyclotriphosphazene is 2:
3.
3. The highly flame-retardant composite material for FPC reinforcement plate according to claim 1, characterized in that: The preparation method of the modified 2-carboxyethylphenylphosphorous acid is as follows: 40 parts of decanediamine are placed in 80 parts of water according to the mass fraction, and the mixture is cooled and stirred at a temperature of 4° C., a stirring rate of 200-250 r / min, and a stirring time of 70-80 min to obtain a mixed solution; Then 30 parts of 2-carboxyethylphenyl hypophosphorous acid are added to the mixed solution, heated and stirred at a temperature of 85° C., a stirring rate of 200-250 r / min, and a stirring time of 10-12 h. After cooling to room temperature, the solution is filtered, washed, and dried at 90° C. for 10 h to obtain modified 2-carboxyethylphenyl hypophosphorous acid.
4. The highly flame-retardant composite material for FPC reinforcement plate according to claim 1, characterized in that: The preparation method of the modified hexaphenoxy cyclotriphosphazene comprises the following steps: S41. According to the mass fractions, 693 parts of hexaphenoxy cyclotriphosphazene and 124 parts of γ-(methacryloyloxy)propyltrimethoxysilane are added to 1200 parts of acetone, and the temperature is raised to 75-80°C under nitrogen protection, and the temperature is kept for 1-1.3 hours. Then, 0.8 parts of azobisisoheptanenitrile are dissolved in 20 parts of acetone to obtain an azobisisoheptanenitrile solution, and the azobisisoheptanenitrile solution is slowly added dropwise within 1 hour, and then after reacting for 10-12 hours, the acetone is removed by rotary evaporation to obtain γ-(methacryloyloxy)propyltrimethoxysilane-modified hexaphenoxy cyclotriphosphazene; S42. Dry nano-silica with a particle size of 20-30 nanometers at 100-120°C for 6-8 hours according to the mass fraction, then add 50 parts of the dried nano-silica and 200 parts of γ-(methacryloyloxy)propyltrimethoxysilane-modified hexaphenoxycyclotriphosphazene to 1500 parts of anhydrous ethanol, stir evenly, and reflux at 78-82°C for 16-20 hours under nitrogen protection. After the reaction is completed, filter, wash with ethanol, and dry to obtain modified hexaphenoxycyclotriphosphazene.
5. The highly flame-retardant composite material for FPC reinforcement plate according to claim 1, characterized in that: The preparation method of the modified glass fiber comprises the following steps: S51. According to the mass fraction, 100 parts of chopped glass fibers with a length of 3-4 mm and a diameter of 9-12 μm are placed in 350 parts of a 25% hydrogen peroxide solution, and then heated at 105-110° C. for reaction for 3-4 hours; after the reaction is completed, the pre-modified glass fibers are obtained by filtering and drying; S52, according to the mass fraction, put 100 parts of the pre-modified glass fiber into 1000 parts of a polydimethyldiallylammonium chloride aqueous solution with a mass concentration of 3.5-4.0%, stir for 1-2 hours, filter, wash and dry to obtain the pre-modified glass fiber; S53. Disperse 50 parts of silica with an average particle size of 20-30 nanometers and 100 parts of pre-modified glass fibers in a solution consisting of 200 parts of ethanol and 500 parts of water, and stir for 2-3 hours. Then, add 3.5 parts of vinyltriethoxysilane, adjust the pH of the solution to 5-6, stir for 4-5 hours, and obtain modified glass fibers by centrifugation, washing, and drying.
6. The highly flame-retardant composite material for FPC reinforcement plate according to claim 1, characterized in that: The coupling agent is composed of γ-aminopropyltrimethoxysilane, anilinemethyltriethoxysilane and N-aminoethyl-γ-aminopropyltriethoxysilane in a mass ratio of 3:3:
2.
7. The highly flame-retardant composite material for FPC reinforcement plate according to claim 1, characterized in that: The lubricant is PE wax.
8. The highly flame-retardant composite material for FPC reinforcement plate according to claim 1, characterized in that: The toughening agent is maleic anhydride grafted ultra-low density polyethylene, and the mass percentage of maleic anhydride groups in the maleic anhydride grafted ultra-low density polyethylene is 1-2%.
9. The highly flame-retardant composite material for FPC reinforcement plate according to claim 1, characterized in that: The antioxidant is bis(2,4-dicumylphenyl)pentaerythritol diphosphite.
10. A method for preparing a highly flame-retardant composite material for an FPC reinforcement plate as claimed in any one of claims 1 to 9, characterized in that: The following steps are involved: S101, adding each raw material into a high-speed mixer according to the mass fraction and mixing them evenly to obtain a premix; S102, melting the premix at an extrusion temperature of 260-275° C. in a twin-screw extruder, extruding and granulating the premix at a rotation speed of 400-450 rpm in the twin-screw extruder, and obtaining a highly flame-retardant composite material for an FPC reinforcement plate.
Citation Information
Patent Citations
Expansive type dripping-resistant flame retardant and preparation method thereof
CN104262620A
Light halogen-free flame-retardant reinforced polyamide composition and preparation method thereof
CN108239394A
Linear polyphosphazene halogen-free flame-retardant toughening modified glass fiber reinforced polyamide 6 / polyamide 66 composite material
CN116333486A
Self-lubricating high-wear-resistance PCR (Polymerase Chain Reaction) polymer composite material as well as preparation method and application thereof
CN118307946A